A role of complexin-lipid interactions in membrane fusion - Seiler, Florian (2009)
Complexins and synaptotagmins regulate calcium-dependent exocytosis. A central helix in complexin confers specific binding to the SNARE fusion machinery. An accessory helix in the amino-terminal region inhibits membrane fusion by blocking SNAREpin zippering. We now show that an amphipathic helix in the carboxy-terminal region of complexin I binds lipid bilayers and affects SNARE-mediated lipid mixing in a liposome fusion assay. The substitution of a hydrophobic amino acid within the helix by a charged residue abolishes the lipid interaction and the stimulatory effect of complexin I in liposome fusion. In contrast, the introduction of the bulky hydrophobic amino acid tryptophan stimulates lipid binding and liposome fusion. This data shows that local complexin-lipid interactions can play a role in membrane fusion.